Tweens' online privacy risks and the role of parental mediation - Faber, Ronald J. (2013)
This study examined the role of parental mediation in tweens' online information disclosing behaviors. In particular, the influence of parental mediation on 2 types of personally identifiable information disclosure (voluntary disclosure in general online activities and disclosure upon marketers' request) was examined. A survey conducted with 381 parent-tween dyads in Korea revealed that, while parental mediation was not directly associated with tweens' information disclosing behaviors, parent-tween disagreement on restrictive mediation was: tweens' inaccurate perception of what parents do to limit their access to commercial Web sites seems to be positively related to tweens' information disclosure on the Web.